Nuclear thiol redox systems in plants. (February 2016) - Delorme-Hinoux, Valérie; Bangash, Sajid A.K.; Meyer, Andreas J.; Reichheld, Jean-Philippe
Highlights: This review gives an overview of the thiol reduction system in the plant nucleus. Nuclear thioredoxin and glutaredoxin targets are overviewed. The plant nucleus contains a glutathione reductase. Abstract: Thiol-disulfide redox regulation is essential for many cellular functions in plants. It has major roles in defense mechanisms, maintains the redox status of the cell and plays structural, with regulatory roles for many proteins. Although thiol-based redox regulation has been extensively studied in subcellular organelles such as chloroplasts, it has been much less studied in the nucleus. Thiol-disulfide redox regulation is dependent on the conserved redox proteins, glutathione/glutaredoxin (GRX) and thioredoxin (TRX) systems. We first focus on the functions of glutathione in the nucleus and discuss recent data concerning accumulation of glutathione in the nucleus. We also provide evidence that glutathione reduction is potentially active in the nucleus. Recent data suggests that the nucleus is enriched in specific GRX and TRX isoforms. We discuss the biochemical and molecular characteristics of these isoforms and focus on genetic evidences for their potential nuclear functions. Finally, we make an overview of the different thiol-based redox regulated proteins in the nucleus. These proteins are involved in various pathways including transcriptional regulation, metabolism and signaling.